Portraits of the Filipina [videorecording] - Cultural Center of the Philippines; Almendralejo, Albert; Brown, Lydia B.; Concepcion, Rowena E.; Roxas. Ma. Theresa E. ([Manila] The Center, 1989)
A performance of CCP residents on stage as a tribute to the Filipino women.
VHS.
Host Helen Vela; music by Inang Laya; choreographer, Alice Reyes.
Keywords: Inang Laya (Singing group); Ballet Philippines; Philippine drama (Filipino); Filipino women; Women -- Social conditions. -- Philippines; MUSIC; HUMANITIES; THEATER ARTS